Evaluation of management effectiveness of Esperanza Marine Sanctuary and Puertobello Fish Sanctuary in Camotes Islands, Cebu, Philippines - Valles, Riva G. (Cebu City University of the Philippines in the Visayas-Cebu College, 2007)
Marine protected areas are proliferating everywhere in the world because of its benefits to fisheries management and coastal conservation. However, very few of the protected areas worldwide are managed effectively that many became paper parks, hence this study. Themanagement effectiveness of two of the six sanctuaries in Camotes-Esperanza Marine Sanctuary and Puertobello Fish sanctuary were evaluated to come up with recommendations that may be used to enable and support adaptive approach to management, improve resource allocation and promote governance thus avoiding the pitfalls of paper parks. The organizational set up of EMS and PFS was described. Their management effectiveness rated using a scorecard modified from World Commission on Protected Area's (WCPA) Evaluating effectiveness A Framework for Assessing the Management of Protected Areas and World Bank's Score Card to Assess Progress in Achieving Management Effectiveness Goals for Marine Protected Area. The assessment was supplemented with information gathered from Key Informant Interview and Focus Group Discussion as well as secondary biophysical data and MPA reportsLikewise the socio-economic condition, the knowledge and perception of the marine resource and marine protected area was determined through a .household interviiew with a questionnaire based on IUCN's How is Your MPA doing? A Guidebook of Natural and Social indicators for Evaluating Marine Protected Area Management Effectiveness. The respondents' incomes come from combined fishing and farming. Fishing is done in the waters off each of the barangay which is part of their traditional fishing grounds and where the MPAs currently are. fish and vegetables are their main food component. although a great majority of the fisherfolks-respondents only have elementary education, yet, the survey showed that they have good knowledge and perception of their marien environment and onamrine sanctuaries concepts. They also have good perception overnon-use value and non-market value of coastal resources serving as good indicators for their likely support of the sanctuary. However, the survey points to the respondents' dominant perception of decreasing catch.Overall, management effectiveness of EMS and PFS was rated as fair despite the above mentioned good indicators. The presence of assisting institutions does not therefore guarantee effective management. Key to an MPA's success is ot only the financial support from LGUs but also on sustained initiative by the managing body to source funds for uninterrupted implementation of programs. Leadership must also make the community involved, especially in making well-informed decisions for the sanctuary.
Thesis (M.S. Environmental Studies) -- Cebu City : U. P. in the Visayas-Cebu College, May 2007.